Animals in Greek, Arabic, and Latin philosophy (Leiden ; Boston)
vii, 636 sayfa
Keywords: “Non-human animals are a topic of intense philosophical interest in the modern day. It is often supposed that this is a recent development, but in fact pre-modern philosophers were intensely interested in animals. Aristotle initiated a long-standing zoological tradition, but it was only part of the vast literature on animals in antiquity and the middle ages. To do it justice, this book gathers twenty-five studies of animals in Greek, Arabic, and Latin philosophy. Major themes include the cognitive capacities of animals, the difference between humans and animals and the question of how humans should treat animals, as well as God's relationship towards animals, animal diet and mating, language among animals, animal suffering, animals as ethical exemplars, and reincarnation.“ --